Combined two-centre experience of single-entry telescopic rods identifies characteristic modes of failure. (August 2020) - Cox, India; Al Mouazzen, Louay; Bleibleh, Sabri; Moldovan, Radu; Bintcliffe, Fiona; Bache, C. Edward; Thomas, Simon
Abstract : Aims: The Fassier Duval (FD) rod is a third-generation telescopic implant for children with osteogenesis imperfecta (OI). Threaded fixation enables proximal insertion without opening the knee or ankle joint. We have reviewed our combined two-centre experience with this implant. Methods: In total, 34 children with a mean age of five years (1 to 14) with severe OI have undergone rodding of 72 lower limb long bones (27 tibial, 45 femoral) for recurrent fractures with progressive deformity despite optimized bone health and bisphosphonate therapy. Data were collected prospectively, with 1.5 to 11 years follow-up. Results: A total of 24 patients (33%) required exchange of implants (14 femora and ten tibiae) including 11 rods bending with refracture. Four (5%) required reoperation with implant retention. Loss of proximal fixation in the femur and distal fixation in the tibia were common. Four patients developed coxa vara requiring surgical correction. In total, 13 patients experienced further fractures without rod bending; eight required implant revision. There was one deep infection. The five-year survival rate, with rod revision as the endpoint, was 63% (95% confidence interval (CI) 44% to 77%) for femoral rods, with a mean age at implantation of 4.8 years (1.3 to 14.8), and 64% (95% CI 36% to 82%) for tibial rods, with a mean age at implantation of 5.2 years (2.0 to 13.8). Conclusion: FD rods are easier to implant but do not improve on the revision rates reported for second generation T-piece rods. Proximal femoral fixation is problematic in younger children with a partially ossified greater trochanter. Distal tibial fixation typically fails after two years. Future generation implants should address proximal femoral and distal tibial fixation to avoid the majority of complications in this series. Cite this article: Bone Joint J 2020;102-B(8):1048–1055.